INTERACTIONAL TEACHING STYLE AS AN INTERDISCIPLINARY APPROACH TO STUDENT LEARNING CHARACTERISTICS - Junaedi, Achmad (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the efforts of teachers to apply interactive teaching style as an interdisciplinary approach to identify student learning characteristics. This research includes phenomenological research with a qualitative approach. The research location was conducted at MTs. Raudhatun Nasihah, Alassumur Kulon Village, Kraksaan District, Probolinggo . Data collection techniques were carried out through a process of observation, in-depth interviews with 4 informants, and documentation. The data analysis technique uses the Miles and Huberman Interactive Model with data reduction activities, data presentation, and drawing conclusions. Data validity with source and technique triangulation process. The results of this study concluded that to identify student characteristics, the teacher made several efforts in the interactive learning process, namely by giving pleasant expressions and being a good listener to students. Of course, the identification of student character is reviewed from 3 main aspects, namely cognitive, affective, and psychomotor aspects of students. This research is a new breakthrough to be able to develop teaching styles of educators to get to know, explore, and develop interests and talents according to student characteristics.